Rebecca Belmore unrolling plastic during the performance of reservoir: reservoir - Belmore, Rebecca (Creator); Addison, Merle (Photographer) (grunt gallery, 2001)
reservoir was a durational work by Rebecca Belmore. In it she used recycled jars to collect water and stockpile it in the space. The reservoir remained in the gallery as an installation for the following week. Belmore is a member of the Lac Seul First Nation (Anishinaabe), and is an internationally recognized multidisciplinary artist. More of her work can be seen at : http://www.rebeccabelmore.com Event host: grunt gallery; Analog Object Catalog Number: 2001.1020 RES